A (des)construção da noção de gênero nos contos de Katherine Mansfield - Gonçalves, Letícia de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study analyzes of the short stories from the collection Bliss & other stories (1920), by the New Zealand author Katherine Mansfield (1888 - 1923), proposing the verification of the deconstruction of gender roles and of the historically categorized discourses in the narratives, and considering the constitution of male and female characters and their relationships. Therefore, we address the relationship between characters of both sexes, the different points of view, the symbols, and, from these concepts, we observe that the categorization of gender and sex is a result of social developments. In pondering the representation of gender in Mansfield's narratives, we expand the matter to social instances, since literature is the representation of the perspective on reality. We use, as a theoretical basis, Virginia Woolf's feminist criticism, Judith Butler's gender performativity and the concept of exotopy by Mikhail Bakhtin, in order to assess the cultural aspects of the gender issue, the literary tradition of women's writing, the ideological identifications and the creation of fictional characters

O presente trabalho pretende fazer uma análise dos contos da coletânea Bliss & other stories (1920), da autora neozelandesa Katherine Mansfield (1888 - 1923). Propomos a verificação da desconstrução da noção de gênero e dos discursos historicamente categorizados nas narrativas, considerando a constituição dos personagens dos sexos masculino e feminino e suas relações. Abordamos a relação entre personagens de ambos os sexos, os distintos focos narrativos, os símbolos, e, a partir de tais apontamentos, observamos que a categorização de gênero e de sexo é resultado de desdobramentos sociais. Ao ponderarmos a representação do gênero nas narrativas mansfieldianas, estamos ampliando a questão para as instâncias sociais, uma vez que a literatura é a representação de perspectivas do real. Tomamos como base teórica a crítica feminista de Virginia Woolf, a teoria da performatividade de Judith Butler e o conceito de exotopia de Mikhail Bakhtin, a fim de avaliarmos os aspectos culturais de gênero, a tradição literária de autoria feminina, as identificações ideológicas e a constituição de personagens ficcionais
Keywords: Mansfield, Katherine 1888-1923; Mulheres e literatura; Literatura inglesa; Representações sociais; Women and literature